Evaluation of the Added Value from Risk Diversification through AEC Capital Market Integration using Stochastic Dominance - Nittayagasetwat, Aekkachai; Buranasiri, Jiroj (International Journal of Economics and Financial Issues, 2017)
This research paper investigates the benefit of risk diversification under the increase in the integration of AEC countries' capital markets during 1999 and 2016. The evidences from the correlation and mean-variance analysis confirm the higher stock market integration. However, the empirical results from Stochastic Dominance technique show that the equally weighted portfolio built from combining the stock index portfolios of five AEC countries has lower ability to dominate stock index portfolio of each AEC country. In other words, the value from combining AEC countries' stock markets is decreasing Keywords: Integration, Mean-Variance Analysis, Stochastic Dominance JEL Classifications: F3, G1